Multi-element synergistic flame-retardant modified coating and preparation method thereof
By surface modification of zinc borate, Mg(OH)2 and Al(OH)3, a multi-composite flame retardant modified organic flame retardant is formed, which solves the problems of poor compatibility and high addition amount inorganic nanoparticles, achieves high efficiency flame retardant and good dispersion, and improves the mechanical properties of the coating.
Patent Information
- Application Number
- CN202411774304.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-05
AI Technical Summary
While improving the flame retardant performance, it is difficult to solve the problem of poor compatibility and easy agglomeration of inorganic nanoparticles with polymer matrix while improving the flame retardant performance. The amount of inorganic flame retardant is added is relatively high, which affects the mechanical properties of the coating.
By surface modification of zinc borate, Mg(OH)2 and Al(OH)3, an organic flame retardant modified multivariate flame retardant is formed, which promotes its effective recombination and dispersion in flame retardant coatings, and forms an inorganic-organic-inorganic multivariate collaborative flame retardant.
The dual goals of high-efficiency flame retardant and good dispersion are achieved, the amount of inorganic flame retardant is added is reduced, and the mechanical properties and flame retardant effect of the coating are improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of flame retardant coatings, and in particular relates to a multi-component synergistic flame retardant modified coating and a preparation method thereof. Background Art
[0002] As a material that can curb the spread of fire, flame retardant coatings have been widely used in many fields. According to statistics, more than 80% of fatalities caused by fires are caused by thick smoke and toxic gases released by burning materials. Therefore, flame retardant coatings must not only have excellent flame retardant properties, but also meet the strict requirements of low toxicity and low smoke. In view of this, the use of traditional organic halogen flame retardants is gradually decreasing due to their high toxicity and high smoke generation, while inorganic flame retardants such as Mg(OH)2 and Al(OH)3 have ushered in rapid development due to their non-toxic and smoke-eliminating properties. However, Mg(OH)2 and Al(OH)3 need to be added to a higher proportion (usually up to 50% by mass) to show a good flame retardant effect, which often leads to a decrease in the processing performance of the base resin and a significant loss of mechanical properties.
[0003] As an important member of the inorganic flame retardant system, zinc borate not only has multiple functions such as flame retardancy, carbonization, smoke suppression, smoldering suppression and droplet formation prevention, but also has the advantages of environmental protection, economy and little effect on the mechanical properties of polymers. Current research often adds zinc borate as a flame retardant additive to inorganic flame retardants to form compound flame retardants, aiming to maintain flame retardant properties while reducing the amount of substances such as Mg(OH)2, thereby improving the mechanical properties of the coating. However, directly mixing zinc borate with Mg(OH)2 and / or Al(OH)3 to form a compound flame retardant cannot solve the problem of poor compatibility and easy agglomeration between inorganic nanoparticles and polymer matrices, and when inorganic flame retardants are directly compounded, the amount of flame retardant added is still high. For example, the synergistic effect of zinc borate with Mg(OH)2 and Al(OH)3 in flame retardant EVA (VA content 24%) shows that even in an intumescent flame retardant system, the amount of flame retardant added needs to reach about 30% to achieve an ideal flame retardant effect.
[0004] Therefore, developing efficient surface modification technologies for inorganic particles such as zinc borate, Mg(OH)2, and Al(OH)3 to achieve the dual goals of efficient flame retardancy and good dispersibility, and promoting these flame retardants to form an effective composite system, is of far-reaching significance for promoting their widespread application in the field of flame retardant coatings. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the existing flame retardant coatings mentioned in the above background technology. The present invention provides a multi-component synergistic flame retardant modified coating and a preparation method thereof; by effectively modifying the surfaces of zinc borate, Mg(OH)2, and Al(OH)3 respectively, while improving their flame retardant properties and dispersibility, and promoting their effective compounding to form an inorganic-organic-inorganic multi-component synergistic flame retardant, a new type of high-performance flame retardant modified material is provided for the field of flame retardant coatings.
[0006] The present invention is achieved through the following technical scheme: a multi-component synergistic flame-retardant modified coating and a preparation method thereof, characterized in that, in parts by weight, it comprises the following components: 80 to 100 parts of water-based epoxy resin, 10 to 20 parts of multi-component composite flame retardant, 40 to 50 parts of curing agent, and 10 to 15 parts of deionized water.
[0007] The multi-component composite flame retardant is composited by organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and organic flame retardant modified zinc borate.
[0008] Preferably, the organic flame retardant modified Al(OH)3(Mg(OH)2) is prepared by the following steps: (a) Add epoxysilane (KH-560) to a mixed solution of water and methanol, and add an organic acid (such as formic acid, acetic acid, etc.), adjust the pH value of the solution to 3.85-4.2, and finally add Al(OH)3 (or Mg(OH)2) nanoparticles, disperse them uniformly by ultrasonication, and heat the reaction solution at 50-80 o C for 6 to 10 hours, followed by suction filtration, multiple washings with deionized water, and drying to obtain epoxy-modified Al(OH)3 (or Mg(OH)2) nanoparticles; the dosage of each component is as follows: for every 0.2 to 0.5 g of KH-560, 200 to 300 mL of a mixed solution of water and methanol in a volume ratio of 2 to 4:1 is added, and 6 to 10 g of inorganic nanoparticles are added.
[0009] (b) adding the epoxy-modified nanoparticles prepared above into dimethyl sulfoxide and 2-amino-4,6-dichloro-S-triazine, and uniformly dispersing the mixture by ultrasonication, and then heating at 80 to 120 °C. o C, stirred for 6 to 10 hours, filtered, washed with deionized water for multiple times, and dried to obtain organic flame retardant modified Al(OH)3 (or Mg(OH)2) nanoparticles; the dosage of each component is as follows: 100 to 200 mL of dimethyl sulfoxide is added to every 1 to 1.5 g of epoxy-modified nanoparticles, and 0.6 to 1 g of 2-amino-4,6-dichloro-S-triazine is added.
[0010] Preferably, the organic flame retardant modified zinc borate is prepared by the following steps: Disperse zinc borate in deionized water, add tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjust the solution pH to 8-9, then add dopamine hydrochloride, and heat the reaction solution at 20-40 o C, stirred for reaction for 2 to 4 hours, filtered, washed with deionized water for multiple times, and dried to obtain polydopamine-modified zinc borate; the dosage of each component is as follows: 1 to 2 g of zinc borate is dispersed in 100 to 200 ml of deionized water, and 0.05 to 0.1 g of dopamine hydrochloride is added.
[0011] Preferably, the multi-component composite flame retardant is prepared by the following steps: Organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 nanoparticles are dispersed in ethanol, and ultrasonically uniformly obtained a dispersion with a mass fraction of 10-20%. Organic flame retardant modified zinc borate is further ultrasonically dispersed in the prepared dispersion, stirred for 1-3 hours, filtered, the solid matter is retained, washed, and dried to obtain a multi-component composite flame retardant composed of Al(OH)3, Mg(OH)2, organic flame retardant modifier (triazine structure and polydopamine), and zinc borate; wherein the mass ratio of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2, and organic flame retardant modified zinc borate is 4-7:4-7:1.
[0012] The preparation method of the above-mentioned multi-component synergistic flame retardant modified coating of the present invention comprises the following steps: A water-based epoxy resin, a multi-component composite flame retardant and deionized water are mixed to obtain a prefabricated coating; the prefabricated coating and a curing agent are mixed to obtain a multi-component synergistic flame retardant modified coating.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) In the composite flame retardant provided by the present invention, zinc borate can form a strong and stable chemical bond with the hydroxyl and amine groups on the surface of organic flame retardant-modified Al(OH)3 and Mg(OH)2 nanoparticles through the phenol and quinone groups in the polydopamine molecules on its surface, thereby forming an effective composite system and promoting the excellent synergistic flame retardant effect of each component; (2) The multi-component composite flame retardant provided by the present invention can not only construct a multi-component high-efficiency flame retardant synergistic system of Al(OH)3-Mg(OH)2-organic flame retardant (triazine structure and polydopamine)-zinc borate, but also, under high temperature conditions, zinc borate and the chlorine atoms in the modifier 2-amino-4,6-dichloro-S-triazine can react to generate a free radical terminator, zinc chloride. This reaction can further enhance the flame retardant effect. (3) The multi-component composite flame retardant provided by the present invention not only has a highly effective flame retardant effect but also has good dispersibility. At the same time, it solves the problem of the influence of large-scale addition and severe agglomeration of inorganic flame retardants such as Al(OH)3 and / or Mg(OH)2 on the mechanical properties of the coating, and effectively promotes the application of inorganic nanoparticles in the field of flame retardant coatings. DETAILED DESCRIPTION
[0014] The present invention is illustrated by the following examples, but the examples are only used for illustration and cannot be regarded as limiting the scope of the invention or the application method of the invention. Unless otherwise specified, the raw materials of the present invention are commercially available. In addition, the water-based epoxy resin emulsion and curing agent can be used in the market. Refer to the instructions for use provided by the manufacturer. Example
[0015] A multi-component synergistic flame retardant modified coating comprises the following components in parts by weight and is prepared by the following steps: 80 parts of waterborne epoxy resin, 10 parts of multi-component composite flame retardant and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a multi-component synergistic flame retardant modified coating.
[0016] The multi-component composite flame retardant is composed of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and organic flame retardant modified zinc borate.
[0017] The organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 are prepared by the following steps: a. Add 0.2 g of epoxysilane (KH-560) to a mixed solution of 200 mL of water and methanol (volume ratio of the two is 2:1), and add formic acid to adjust the pH value of the solution to about 4, preferably 3.85-4.2. Finally, add 6 g of Al(OH)3 (or Mg(OH)2) nanoparticles, disperse them evenly by ultrasonication, and heat the reaction solution at 50 o After stirring and reacting for 10 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain epoxy-modified Al(OH)3 (or Mg(OH)2) nanoparticles; b. 1 g of the epoxy-modified nanoparticles prepared above was added to 100 mL of dimethyl sulfoxide, and 0.6 g of 2-amino-4,6-dichloro-S-triazine was added, the mixture was ultrasonically dispersed uniformly, and then heated at 80 o After stirring and reacting for 10 h at 37°C, the mixture was filtered, washed with deionized water for several times, and dried to obtain organic flame retardant modified Al(OH)3 (or Mg(OH)2) nanoparticles; The organic flame retardant modified zinc borate is prepared by the following steps: Disperse 1 g of zinc borate in 100 mL of deionized water, add tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjust the pH of the solution to 8, then add 0.05 g of dopamine hydrochloride, and heat the reaction mixture at 20 o C, stirred and reacted for 4 h, and then filtered, washed with deionized water for multiple times, and dried to obtain polydopamine-coated zinc borate; The multi-component composite flame retardant is prepared by the following steps: 4g of the prepared organic flame retardant modified Al(OH)3 and 4g of organic flame retardant modified Mg(OH)2 nanoparticles were dispersed in ethanol and ultrasonically dispersed to obtain a dispersion with a mass fraction of 10%. Further, 1g of organic flame retardant modified zinc borate was ultrasonically dispersed in the prepared dispersion, stirred for 3h, filtered, the solids were retained, washed, and dried to obtain a multi-component composite flame retardant consisting of Al(OH)3, Mg(OH)2, organic flame retardant modifier (triazine structure and polydopamine), and zinc borate. Example
[0018] A multi-component synergistic flame retardant modified coating comprises the following components in parts by weight and is prepared by the following steps: 90 parts of waterborne epoxy resin, 15 parts of multi-component composite flame retardant and 12.5 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 45 parts of a curing agent are added and stirred evenly to obtain a multi-component synergistic flame retardant modified coating.
[0019] The multi-component composite flame retardant is composed of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and organic flame retardant modified zinc borate.
[0020] The organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 are prepared by the following steps: a. Add 0.35g epoxysilane (KH-560) to a mixed solution of 250mL water and methanol (volume ratio of the two is 3:1), and add acetic acid to adjust the pH value of the solution to about 4, preferably 3.85-4.2, and finally add 8g Al(OH)3 (or Mg(OH)2) nanoparticles, disperse them uniformly by ultrasonication, and heat the reaction solution at 65 o After stirring and reacting for 8 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain epoxy-modified Al(OH)3 (or Mg(OH)2) nanoparticles; b. 1.25 g of the epoxy-modified nanoparticles prepared above were added to 150 mL of dimethyl sulfoxide, and 0.8 g of 2-amino-4,6-dichloro-S-triazine was added, the mixture was ultrasonically dispersed, and then at 100 oAfter stirring and reacting for 8 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain organic flame retardant modified Al(OH)3 (or Mg(OH)2) nanoparticles; The organic flame retardant modified zinc borate is prepared by the following steps: Disperse 1.5 g of zinc borate in 150 mL of deionized water, add tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjust the solution pH to 8.5, then add 0.075 g of dopamine hydrochloride, and heat the reaction mixture at 30 o C, stirred and reacted for 3 h, and then filtered, washed with deionized water for multiple times, and dried to obtain polydopamine-coated zinc borate; The multi-component composite flame retardant is prepared by the following steps: 5.5 g of the prepared organic flame retardant modified Al(OH)3 and 5.5 g of organic flame retardant modified Mg(OH)2 nanoparticles were dispersed in ethanol and ultrasonically dispersed to obtain a dispersion with a mass fraction of 15%. Further, 1 g of organic flame retardant modified zinc borate was ultrasonically dispersed in the prepared dispersion, stirred for 2 h, filtered, the solids were retained, washed, and dried to obtain a multi-component composite flame retardant consisting of Al(OH)3, Mg(OH)2, organic flame retardant modifier (triazine structure and polydopamine), and zinc borate. Example
[0021] A multi-component synergistic flame retardant modified coating comprises the following components in parts by weight and is prepared by the following steps: 100 parts of waterborne epoxy resin, 20 parts of multi-component composite flame retardant and 15 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 50 parts of a curing agent are added and stirred evenly to obtain a multi-component synergistic flame retardant modified coating.
[0022] The multi-component composite flame retardant is composed of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and organic flame retardant modified zinc borate.
[0023] The organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 are prepared by the following steps: a. Add 0.5 g epoxysilane (KH-560) to a mixed solution of 300 mL water and methanol (volume ratio of the two is 4:1), and add formic acid to adjust the pH value of the solution to about 4, preferably 3.85-4.2. Finally, add 10 g Al(OH)3 (or Mg(OH)2) nanoparticles, disperse them evenly by ultrasonication, and heat the reaction solution at 80 o After stirring and reacting for 6 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain epoxy-modified Al(OH)3 (or Mg(OH)2) nanoparticles; b. 1.5 g of the epoxy-modified nanoparticles prepared above were added to 200 mL of dimethyl sulfoxide, and 1 g of 2-amino-4,6-dichloro-S-triazine was added, the mixture was ultrasonically dispersed uniformly, and then heated at 120 o After stirring and reacting for 6 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain organic flame retardant modified Al(OH)3 (or Mg(OH)2) nanoparticles; The organic flame retardant modified zinc borate is prepared by the following steps: Disperse 2 g of zinc borate in 200 mL of deionized water, add tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjust the solution pH to 9, then add 0.1 g of dopamine hydrochloride, and heat the reaction solution at 40 o C, stirred and reacted for 2 h, and then filtered, washed with deionized water for multiple times, and dried to obtain polydopamine-coated zinc borate; The multi-component composite flame retardant is prepared by the following steps: 7g of the prepared organic flame retardant modified Al(OH)3 and 7g of organic flame retardant modified Mg(OH)2 nanoparticles were dispersed in ethanol, and ultrasonic dispersion was performed to obtain a dispersion with a mass fraction of 20%. Further, 1g of organic flame retardant modified zinc borate was ultrasonically dispersed in the prepared dispersion, stirred for 1h, filtered, the solid was retained, washed, and dried to obtain a multi-component composite flame retardant consisting of Al(OH)3, Mg(OH)2, organic flame retardant modifier (triazine structure and polydopamine), and zinc borate.
[0024] Comparative Example 1 The comparative coating comprises the following components in parts by mass and is prepared by the following steps: 80 parts of waterborne epoxy resin and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a comparative coating 1.
[0025] Comparative Example 2 The comparative coating comprises the following components in parts by mass and is prepared by the following steps: 80 parts of waterborne epoxy resin, 10 parts of compounded flame retardant and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a comparative 2 coating; wherein the compounded flame retardant is composed of unmodified Al(OH)3 and Mg(OH)2, and the mass ratio of the two is 1:1.
[0026] Comparative Example 3 The comparative coating comprises the following components in parts by mass and is prepared by the following steps: 80 parts of waterborne epoxy resin, 10 parts of compound flame retardant and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a comparative coating 3; wherein the compound flame retardant is composed of unmodified Al(OH)3, Mg(OH)2 and unmodified zinc borate, and the mass ratio of the three is 4:4:1.
[0027] Comparative Example 4 The comparative coating comprises the following components in parts by mass and is prepared by the following steps: 80 parts of waterborne epoxy resin, 10 parts of compounded flame retardant and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a comparative coating 1; wherein the compounded flame retardant is composed of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and unmodified zinc borate, and the mass ratio of the three is 4:4:1.
[0028] The organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 are prepared by the following steps: a. Add 0.2g epoxysilane (KH-560) to a mixed solution of 200mL water and methanol (volume ratio of the two is 2:1), and add formic acid to adjust the pH value of the solution to about 4. Finally, add 6g Al(OH)3 (or Mg(OH)2) nanoparticles and disperse them evenly by ultrasonic. o After stirring and reacting for 10 h at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain epoxy-modified Al(OH)3 (or Mg(OH)2) nanoparticles; b. 1 g of the epoxy-modified nanoparticles prepared above was added to 100 mL of dimethyl sulfoxide, and 0.6 g of 2-amino-4,6-dichloro-S-triazine was added, the mixture was ultrasonically dispersed uniformly, and then heated at 80 o C for 10 h, followed by suction filtration, multiple washings with deionized water, and drying to obtain organic flame retardant modified Al(OH)3 (or Mg(OH)2) nanoparticles.
[0029] Comparative Example 5 The comparative coating comprises the following components in parts by mass and is prepared by the following steps: 80 parts of waterborne epoxy resin, 10 parts of compounded flame retardant and 10 parts of deionized water are mixed and stirred evenly to obtain a prefabricated coating, and then 40 parts of a curing agent are added and stirred evenly to obtain a comparative coating 1; wherein the compounded flame retardant is composed of unmodified Al(OH)3 and Mg(OH)2 and organic flame retardant modified zinc borate, and the mass ratio of the three is 4:4:1.
[0030] The organic flame retardant modified zinc borate is prepared by the following steps: Disperse 1 g of zinc borate in 100 mL of deionized water, add tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjust the pH of the solution to 8, then add 0.05 g of dopamine hydrochloride, and heat the reaction mixture at 20 o C for 4 h, followed by suction filtration, multiple washings with deionized water, and drying to obtain polydopamine-coated zinc borate.
[0031] The coatings obtained in Examples 1-3 and Comparative Examples 1-5 were evenly brushed on the surface of a steel sheet (sandblasting Sa2 level), with the average coating thickness maintained at about 1.5 mm, and cured at room temperature for one week to obtain a sample coating. The morphology and ultimate flame retardant time of each coating preparation process are listed in Table 1. Table 1 Morphology and ultimate fire resistance time of the coatings obtained in Examples 1-3 and Comparative Examples 1-5 method Coating preparation process morphology Ultimate flame retardant time Example 1 Smooth, delicate, no particles attached 37min Example 2 Smooth, delicate, no particles attached 47min Example 3 Smooth, delicate, no particles attached 52min Comparative Example 1 Smooth, delicate, no particles attached 22min Comparative Example 2 A small amount of particles attached 23min Comparative Example 3 A small amount of particles attached 25min Comparative Example 4 Smooth, delicate, no particles attached 30min Comparative Example 5 A small amount of particles attached 27min By comparing the results of the embodiments and the comparative examples, it can be clearly seen that the multi-component composite flame retardant prepared by the present invention exhibits significant advantages. The flame retardant not only effectively compounds the components together through a strong chemical bond, but also gives full play to the efficient flame retardant synergistic effect between flame retardant components such as Al(OH)3, Mg(OH)2, triazine structure, polydopamine, halogen and zinc borate, and this synergistic effect promotes the formation of a denser carbon layer. In addition, the surface of the composite flame retardant is rich in a large number of active functional groups, which can form a strong interaction with the resin matrix, thereby significantly improving the compatibility between the flame retardant and the matrix. Therefore, the coating prepared by the present invention exhibits excellent flame retardant properties. In contrast, unmodified Al(OH)3 and Mg(OH)2 were used as composite flame retardants in Comparative Example 2, and it can be seen that a small amount of addition has a very limited effect on the improvement of the flame retardant properties of the coating. Comparative Example 3 further adds magnesium silicate, but due to the weak interaction between unmodified Al(OH)3, Mg(OH)2 and magnesium silicate, and the easy agglomeration phenomenon, the flame retardant performance of the obtained coating is not significantly improved. In Comparative Examples 4 and 5, Al(OH)3, Mg(OH)2 and zinc borate fail to form an effective composite, so their synergistic flame retardant effect cannot be fully exerted, and the flame retardant performance of the coating is naturally not as good as the coating in the embodiment. In summary, the multi-component composite flame retardant of the present invention shows obvious advantages in improving the flame retardant performance of coatings.
[0032] The present invention is not limited to the above-mentioned specific implementation modes. For ordinary technicians in this field, various changes made based on the above-mentioned conception without creative work all fall within the protection scope of the present invention.
Claims
1. A multi-component synergistic flame retardant modified coating, characterized in that: The multi-component synergistic flame-retardant modified coating comprises the following components by weight: 80-100 parts of water-based epoxy resin, 10-20 parts of multi-component composite flame retardant, 40-50 parts of curing agent, and 10-15 parts of deionized water; the multi-component composite flame retardant is composited by organic flame-retardant modified Al(OH)3, organic flame-retardant modified Mg(OH)2 and organic flame-retardant modified zinc borate.
2. The multi-component synergistic flame retardant modified coating according to claim 1, characterized in that: The organic flame retardant modified Al(OH)3 and the organic flame retardant modified Mg(OH)2 are prepared by the following steps: Add epoxysilane (KH-560) to a mixed solution of water and methanol, and add an organic acid to adjust the pH value of the solution to 3.85-4.
2. Finally, add inorganic nanoparticles Al(OH)3 or Mg(OH)2 and disperse them evenly by ultrasonic. o After stirring and reacting for 6 to 10 hours at 40 °C, the mixture was filtered, washed with deionized water for several times, and dried to obtain epoxy-modified Al(OH)3 or Mg(OH)2) nanoparticles; The epoxy-modified nanoparticles prepared in step a are added to dimethyl sulfoxide, and 2-amino-4,6-dichloro-S-triazine is added, the mixture is ultrasonically dispersed uniformly, and then heated at 80 to 120 o C, and then stirred for 6 to 10 hours, filtered, washed with deionized water for several times, and dried to obtain organic flame retardant modified Al(OH)3 or Mg(OH)2 nanoparticles.
3. The multi-component synergistic flame retardant modified coating according to claim 2, characterized in that: The dosage of KH-560, the mixed solution of water and methanol, and the inorganic nanoparticles in step a is as follows: for every 0.2 to 0.5 g of KH-560, add 200 to 300 mL of a mixed solution of water and methanol with a volume ratio of 2 to 4:1, and add 6 to 10 g of inorganic nanoparticles.
4. The multi-component synergistic flame retardant modified coating according to claim 2, characterized in that: The dosage of the epoxy-modified nanoparticles, dimethyl sulfoxide, and 2-amino-4,6-dichloro-S-triazine in step b is as follows: 100-200 mL of dimethyl sulfoxide and 0.6-1 g of 2-amino-4,6-dichloro-S-triazine are added for every 1-1.5 g of epoxy-modified nanoparticles.
5. The multi-component synergistic flame retardant modified coating according to claim 1, characterized in that: The organic flame retardant modified zinc borate is prepared by the following steps: dispersing zinc borate in deionized water, adding tris(hydroxymethyl)aminomethane hydrochloride after ultrasonic dispersion, adjusting the pH value of the solution to 8-9, then adding dopamine hydrochloride, and heating the reaction solution at 20-40°C. o C, stirred for reaction for 2-4 hours, filtered, washed with deionized water for several times, and dried to obtain polydopamine-modified zinc borate.
6. The multi-component synergistic flame retardant modified coating according to claim 5, characterized in that: When preparing the organic flame retardant modified zinc borate, the dosage of zinc borate, deionized water and dopamine hydrochloride is as follows: 1-2g of zinc borate is dispersed in 100-200ml of deionized water, and 0.05-0.1g of dopamine hydrochloride is added.
7. The multi-component synergistic flame retardant modified coating according to claim 1, characterized in that: The multi-component composite flame retardant is prepared by the following steps: dispersing organic flame retardant modified Al(OH)3 and organic flame retardant modified Mg(OH)2 nanoparticles in ethanol, ultrasonically uniformly obtaining a dispersion with a mass fraction of 10-20%, then ultrasonically dispersing organic flame retardant modified zinc borate in the prepared dispersion, stirring for 1-3 hours, filtering, retaining solids, washing, and drying to obtain a multi-component composite flame retardant composed of Al(OH)3, Mg(OH)2, organic flame retardant modifier, and zinc borate.
8. The multi-component synergistic flame retardant modified coating according to claim 7, characterized in that: The mass ratio of organic flame retardant modified Al(OH)3, organic flame retardant modified Mg(OH)2 and organic flame retardant modified zinc borate in the multi-component composite flame retardant is 4-7:4-7:
1.
9. A method for preparing the multi-component synergistic flame retardant modified coating according to claim 1, characterized in that: The preparation method comprises the following preparation steps: A. Mixing waterborne epoxy resin, multi-component composite flame retardant and deionized water to obtain a prefabricated coating; B. Mixing the prefabricated coating and the curing agent to obtain a multi-component synergistic flame retardant modified coating.
Citation Information
Patent Citations
Flame-retardant polymer composite material
CN101463155A
Triazine fire retardant, preparation method and applications thereof
CN106188619A
Halogen-free flame-retardant polyamide composite material and preparation method thereof
CN114181521A
Preparation method of efficient fireproof NH4Cl / Cu-coated BNNSs-based waterborne polyurethane coating
CN117866524A
Synergistic modified polyurethane fireproof coating and preparation method thereof
CN118460081A
Cited By
Concentrated grafted PVC efficient flame-retardant master batch material and preparation method thereof
CN120040893A
Zinc-based composite fireproof coating and preparation method thereof
CN120554926A
Zinc-based composite fireproof coating and preparation method thereof
CN120554926B
Flame-retardant waterproof coiled material PE composite film and preparation method thereof
CN120842653A